PRODUCTION, QUALITY AND MATURITY GRAPE 'Syrah' IN CONDITION SUBTROPICAL OF BRASIL - Pimentel Junior, A.; Domingues Neto, F. J.; Da Silva, M. J. R.; Tecchio, M. A. (Revista Brasileira de Engenharia de Biossistemas, 2019)
Faced with the prospect of revitalizing the wine industry in Brazil, some restrictions on the producers were found, and the lack of knowledge of grape varieties for juice and wine and their behavior in the regional climatic conditions. In this sense, the objective of this study was to evaluate the production, fruit quality and ripeness of the grape 'Syrah' in subtropical region. The experiment was conducted at the Experimental Farm of UNESP in Sao Manuel-SP. The experimental design consisted entirely randomized with five replicates of five plants each. The vines of Syrah grafted on rootstock 'IAC 766' is presented in the third year of production, spacing of 2.0 x 0.80 m and sustained on high trellis system. From the beginning of maturity extending to harvest, they were collected weekly 100 berries per experimental plot for assessing the maturity, determining the content of soluble solids (SS), titratable acidity (AT), pH and SS / AT . At harvest, were evaluated: production, productivity, number of bunches per plant, fresh weight, length and width of clusters, berries and rachis and number of berries per cluster. The characteristics of production, physical and grape maturation 'Syrah', to suggest that this cultivar, in subtropical Brazilian conditions, provides ideal conditions for the production of winemaking.